Leading teleworkers in academia: managers' experiences and expectations for the future - Linda Widar; Eva Boman; Marina Heiden; Birgitta Wiitavaara (Frontiers in Organizational Psychology)
IntroductionTelework is increasing in working life, especially in knowledge intense organizations as academic institutions. Managers are found crucial for performance and wellbeing outcomes in telework, but managers' perspective on leading teleworkers lacks attention.MethodsThis study aimed to investigate academic managers' experiences of leading teleworkers prior to and during the COVID-19 pandemic, and their expectations for future leadership in telework. A qualitative study based on interviews with 16 academic middle managers was performed. Findings were analyzed inductively by a phenomenographic research approach.FindingsThe findings show that leading teleworkers was characterized by demands posed by remote and digital communication; regulation and policies; occupational health and safety management; and new norms for leadership.DiscussionIn conclusion, academic institutions need to improve organizational resources for managers' leading teleworkers to facilitate successful leadership and to secure sustainable work conditions for managers as well as for teleworking employees.